A novel AuNPs colorimetric sensor for sensitively detecting viable Salmonella typhimurium based on dual aptamers. (September 2020) - Chen, Sihan; Yang, Xinyan; Fu, Shiqian; Qin, Xue; Yang, Tao; Man, Chaoxin; Jiang, Yujun
Abstract: A sensitive and accurate strategy was presented based on gold nanoparticles (AuNPs) for visual detecting viable Salmonella typhimurium ( S. typhimurium ). In this paper, dual aptamers were used to capture S. typhimurium and PCR amplification, respectively. The highly stable network structure formed by the hybridization between amplicons and AuNPs-probes protects AuNPs from self-aggregation and color change in the presence of salt. Under optimized conditions, the ratio of the absorbance intensity of AuNPs between A523 and A650 changed regularly with the decrease of pathogen concentration, which showed a linear relationship of S. typhimurium within the concentration ranging from 3.3 × 10 1 to 3.3 × 10 6  CFU/mL. The detection limit of S. typhimurium can be read out by naked eye as low as 33 CFU/mL in pure culture and 95 CFU/mL in spiked milk. The assay performed an accurate and specific diagnosis of positive results without cross-reactivity to dead S. typhimurium and 12 non- S. typhimurium strains. In our perception, this colorimetric sensor would be a promising platform for point-of-care testing (POCT) application of viable S. typhimurium in milk samples. Highlights: A novel and sensitive colorimetrical sensor was established. The assay based on dual aptamers independent of antibodies and DNA extraction. The assay can specifically distinguish live S. typhimurium from dead cells. This sensor was applied to detect S. typhimurium in milk samples.